Risk Aversion and Job Mobility - Thomas M. van Huizen; Rob Alessie (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2016)
Job mobility is inherently risky as workers have limited ex ante information about the quality of outside jobs. Using a large longitudinal Dutch dataset, which includes data on risk preferences elicited through (incentivized) experiments, we examine the relation between risk aversion and job mobility. The results for men show that risk averse workers are less likely to move to other jobs. For women, the evidence that risk aversion affects job mobility is weak. Our empirical findings indicate that the negative relation between risk aversion and job mobility is driven by the job acceptance rather than the search effort decision.
Keywords: 330; Job mobility; risk aversion; job search; risk preferences